Does School Admission by Zoning Affect Educational Inequality? A Study of Family Background Effect in Estonia, Finland, and Sweden. Issue 6 (2nd November 2017) - Põder, Kaire; Lauri, Triin; Veski, Andre
ABSTRACT: We indicate the size of family background effects in Sweden, Finland, and Estonia – countries that differ in both the rhetoric and extensiveness of the system-level school choice policies. Family background effect is defined as the dependence of student achievement on family background characteristics, such as parental education, income, and social status. The number of books at home is used as a proxy when operationalising family background, and its effect is measured as a percentage of individual-level PISA scores. Fixed-effect regression results reveal that family background remains a powerful determinant in the educational results of 15-year-old students in all three cases, being largest in Sweden. Furthermore, we show how the family background effect is moderated by school-level choice policy, that is, how students and schools are matched. The analysis reveals that zoning policies have statistically significant negative effects on the impact of the family background effect, independent of country-level policies.